A new technique to adjust the length of artificial chordae during mitral anterior leaflet repair. Issue 12 (6th November 2022) - Nasso, Giuseppe; Di Bari, Nicola; Bonifazi, Raffaele; Santarpino, Giuseppe; Moscarelli, Marco; Condello, Ignazio; Soletti, Giovanni Jr; Mick, Stephanie; Agrò, Felice; Paparella, Domenico; Gaudino, Mario; Speziale, Giuseppe
Abstract: Background: Length measurement of artificial chordae remains a critical step during mitral valve repair (MVr). The aim of this study is to assess the effectiveness of a new length measuring technique. Methods: All consecutive patients with anterior leaflet prolapse/flail who underwent MVr using the described method between January 2020 and January 2022 at our institution were included in the analysis. Clinical and transesophageal echocardiography data were collected postoperatively and at 1‐year follow‐up. The primary outcome was freedom from mitral regurgitation (MR). Secondary outcomes were presentation with New York Heart Association (NYHA) class <2 and leaflet coaptation length ≥10 mm. Results: Of 25 patients, 16 (64%) were males. A total of 15 (60%) had isolated anterior leaflet disease, while 10 (40%) had concomitant posterior involvement. Twenty patients with isolated MR (80%) underwent right anterior mini‐thoracotomy, while 5 (20%) with associated valvular or coronary disease underwent sternotomy. The median number of chordae implanted was 2 [1–4]. Postrepair intraoperative MR grade was 0 in 23 patients (92%) and 1 in 2 (8%). Thirty‐day mortality was 0%. De novo atrial fibrillation was 20%. At follow‐up, mortality was 0%. No patients presented with moderate or severe MR. A total of 22 patients (88%) were in NYHA class I, while 3 (12%) in class II. The coaptation length was 11 ± 1 mm. Conclusions: The short‐term outcomes of the described technique are good with adequate leaflet coaptation in all treated patients. Long‐term results are needed to assess the stability and durability of this repair technique.